The Effect Of Taxpayer Awareness And Tax Sanctions On Individual Taxpayer Compliance With Risk Preference As A Moderating Variable (Case Study of Employee Class Students majoring in Accounting at Universitas Mercu Buana Meruya Campus class of 2018) - Alytha Pratiwi; Garin Pratiwi Solihati (IAEI, 2023)
The purpose of this study was to determine the effect of taxpayer awareness and tax sanctions on individual taxpayer compliance with risk preference as a moderating variable (case study of Employee Class Students, Department of Accounting, Mercu Buana University class 2018). The population in this study were 199 students in the class of employees majoring in accounting at Mercu Buana University, Meruya Campus in the class of 2018. The sampling technique used non-probability methods with the slovin formula, a sample of 100 respondents. This study uses primary data, namely questionnaires. This study uses a quantitative method with multiple regression analysis model with smartPLS application. The results will show a positive or negative effect on taxpayer awareness and tax sanctions on individual taxpayer compliance with risk preference as a moderating variable.